Evaluating the level of employee engagement in strategy implementation using the Balanced Scorecard - Goitseone Klinck; Martha Esther Moraka (Jurnal Dinamika Sosial Budaya, 2019)
The term ‘employee engagement’ has been debated in human resources management, with particular emphasis on discussions centred on employee motivation, job satisfaction and productivity. Recent research shifted focus to show its significance in performance management. Research is still scanty on the linkage of employee engagement, overall organisation performance and the strategic management process. This research aimed at assessing the role of employee engagement in strategy implementation using the Balanced Scorecard for a Ministry of Minerals Resources. Knowledge of the importance of engagement in the execution of the organisation’s strategy and performance management was sought and the role of leadership in driving employee engagement in the workplace. A quantitative research strategy was used to gather data from a target population of 120 participants through the use of questionnaires. Findings revealed that awareness of the importance of engaged employees in the execution of an organisation strategy is relatively high and can positively contribute to increased productivity and performance, particularly if the Business Scorecard tool is understood by all employees and appropriately cascaded to them. The study also recommended that a positive organisational culture be cultivated so that all employees have the same vision, motivation and drive to improve productivity.